Balancing urban growth and environmental sustainability through spatial planning: A Policy and land use analysis - Putri, Tri Riska (Journal of Placemaking and Streetscape Design, 2025)
Background: Spatial planning is an essential component of regional development, particularly in areas that serve as centers of governance and economic activity. Challenges in sustainable spatial management arise as population growth increases the demand for public facilities, housing, and green open spaces. This study analyzes spatial planning policies with a focus on land use, infrastructure, and environmental impacts. Using a participatory approach, it aims to identify problems and explore potential strategies for more effective spatial planning development. Methods: This study applies a comprehensive literature review method, with data sourced from previous studies and land use maps. The discussion is presented descriptively, referencing relevant scientific literature and reliable sources. Findings: The results are expected to provide recommendations for sustainability-oriented decision-making and contribute to improving the quality of life of urban communities. These efforts are essential to balance development with environmental conservation while also enhancing the attractiveness of urban areas for investment and tourism. Conclusion: Analysis shows that residential land experienced a substantial increase, from 171.44 hectares to 348.17 hectares, reflecting high demand for housing driven by population growth and infrastructure development. Conversely, dry land decreased drastically from 1,566.23 hectares to 305.41 hectares, indicating significant conversion of land for non-agricultural purposes. The reduction of green open land and dry land poses serious risks to food security and environmental quality. Novelty/Originality of this article:  This study emphasizes the importance of implementing sustainable spatial planning policies that balance infrastructure and residential development with ecological preservation and agricultural sustainability. With appropriate strategies, land use can be directed to support sustainable and resilient urban growth.